Catestatin Induces Glucose Uptake and GLUT4 Trafficking in Adult Rat Cardiomyocytes. (2nd October 2018) - Gallo, Maria Pia; Femminò, Saveria; Antoniotti, Susanna; Querio, Giulia; Alloatti, Giuseppe; Levi, Renzo
Abstract : Catestatin is a cationic and hydrophobic peptide derived from the enzymatic cleavage of the prohormone Chromogranin A. Initially identified as a potent endogenous nicotinic–cholinergic antagonist, Catestatin has recently been shown to act as a novel regulator of cardiac function and blood pressure and as a cardioprotective agent in both pre- and postconditioning through AKT-dependent mechanisms. The aim of this study is to investigate the potential role of Catestatin also on cardiac metabolism modulation, particularly on cardiomyocytes glucose uptake. Experiments were performed on isolated adult rat cardiomyocytes. Glucose uptake was assessed by fluorescent glucose incubation and confocal microscope analysis. Glut4 plasma membrane translocation was studied by immunofluorescence experiments and evaluation of the ratio peripheral vs internal Glut4 staining. Furthermore, we performed immunoblot experiments to investigate the involvement of the intracellular pathway AKT/AS160 in the Catestatin dependent Glut4 trafficking. Our results show that 10 nM Catestatin induces a significant increase in the fluorescent glucose uptake, comparable to that exerted by 100 nM Insulin. Moreover, Catestatin stimulates Glut4 translocation to plasma membrane and both AKT and AS160 phosphorylation. All these effects were inhibited by Wortmannin. On the whole, we show for the first time that Catestatin is able to modulate cardiac glucose metabolism, by inducing an increase in glucose uptake through Glut4 translocation to the plasma membrane and that this mechanism is mediated by the AKT/AS160 intracellular pathway.